Phosphates and behavioral abnormalities: correspondence - Maurer, Martin H. (Deutsches Ärzteblatt, 2012)
In their review article, Ritz et al. described the consequences of hyperphosphatemia caused by phosphate additives in food with regard to increased renal and cardiovascular morbidity and mortality (1). I want to add that phosphates for some time have...
Gesehen am 01.08.2024